Synthesis of phenanthridines via a novel photochemically-mediated cyclization and application to the synthesis of triphaeridine - Ntsimango, Songeziwe; Ngwira, Kennedy J.; Bode, Moira L.; de Koning, Charles B. (Beilstein Journal of Organic Chemistry, 2021)
Readily synthesized biphenyl-2-carbaldehyde O-acetyl oximes were exposed to UV radiation affording phenanthridines. The scope and limitations of this novel reaction were explored. For example, exposure of 2',3'-dimethoxy-[1,1'-biphenyl]-2-carbaldehyde O-acetyl oxime to UV radiation afforded 4-methoxyphenanthridine in 54% yield. This methodology was applied to the synthesis of trisphaeridine to afford the product in four linear steps in an overall yield of 6.5% from 1-bromo-2,4,5-trimethoxybenzene.
Keywords: aromatic compounds; cyclization; iminyl radical; phenanthridines; radical cation; synthesis; UV irradiation

(untitled) - Tumir, L.-M.; Radić Stojković, M.; Piantanida, I. (Beilstein J. Org. Chem., 2014)

(untitled) - Pictet, A.; Ankersmit, H. J. (Justus Liebigs Ann. Chem., 1891)

(untitled) - Li, Y.; Zhu, J.; Zhang, L.; Wu, Y.; Gong, Y. (Chem. – Eur. J., 2013)

(untitled) - Ghosh, M.; Ahmed, A.; Dhara, S.; Ray, J. K. (Tetrahedron Lett., 2013)

(untitled) - Pictet, A.; Hubert, A. (Ber. Dtsch. Chem. Ges., 1896)

(untitled) - Morgan, G. T.; Walls, L. P. (J. Chem. Soc., 1931)

(untitled) - Deb, I.; Yoshikai, N. (Org. Lett., 2013)

(untitled) - Alonso, R.; Campos, P. J.; García, B.; Rodríguez, M. A. (Org. Lett., 2006)

(untitled) - McBurney, R. T.; Slawin, A. M. Z.; Smart, L. A.; Yu, Y.; Walton, J. C. (Chem. Commun., 2011)

(untitled) - Walton, J. C. (Acc. Chem. Res., 2014)

(untitled) - An, X.-D.; Yu, S. (Org. Lett., 2015)

(untitled) - Gore, M. P.; Gould, S. J.; Weller, D. D. (J. Org. Chem., 1991)

(untitled) - Ngwira, K. J.; Rousseau, A. L.; Johnson, M. M.; de Koning, C. B. (Eur. J. Org. Chem., 2017)

(untitled) - Walton, J. C. (Molecules, 2016)

(untitled) - de Koning, C. B.; Michael, J. P.; Rousseau, A. L. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Tay, N. E. S.; Nicewicz, D. A. (J. Am. Chem. Soc., 2017)

(untitled) - Walton, J. C. (Molecules, 2016)

(untitled) - Harayama, T.; Akamatsu, H.; Okamura, K.; Miyagoe, T.; Akiyama, T.; Abe, H.; Takeuchi, Y. (J. Chem. Soc., Perkin Trans. 1, 2001)